1019 Eeg Functional Connectivity During Wakefulness And Rem Sleep In Patients With Mild Cognitive Impairment. (27th April 2018) - Lafrenière, A; Brayet, P; Lina, J; Petit, D; Montplaisir, J; Carrier, J
Abstract: Introduction: Mild cognitive impairment (MCI), which is a prodrome of Alzheimer's disease (AD), offers the opportunity to identify AD-related markers before the dementia phase. Cholinergic basal forebrain neurons, which degenerate early in AD, play a major role during Rapid-Eye-Movement (REM) sleep, at a time when several other neuronal systems are less active, leaving the cholinergic influence unmasked. Here we compared EEG functional connectivity (FC) during wakefulness and REM sleep in patients with MCI and in cognitively healthy individuals (CHI). Methods: 32 subjects with MCI (mean age 64 ± 6.1 years) and 32 subjects without cognitive impairment (mean age 63.7 ± 6.6 years) underwent a neuropsychological evaluation, a night of polysomnography and a resting-state EEG recording with 14 EEG electrodes. EEG FC was evaluated with using imaginary coherence analyses performed on manually selected artefact-free epochs in both REM sleep and resting wakefulness. Four frequency bands (delta, theta, alpha and beta) were analysed. Differences between REM sleep and wakefulness were assessed with a Welch's t-stat. A non-parametric test on the max-stat and a permutation resampling allowed to account for multiple comparisons (between pairs of electrodes) in a false discovery rate like thresholding (p<0.04). Results: During resting wakefulness, patients with MCI showed higher FC for the delta band, but slightly lower FC for the alpha band as compared to the CHI. During REM sleep, both groups showed a global FC decrease for the alpha band as compared to wakefulness but this decrease was less prominent in the MCI patients. Conclusion: Compared to CHI, patients with MCI individuals show a reduced ability to decrease FC in alpha during REM sleep with respect to wakefulness. Our results support previous reports showing higher EEG FC during wakefulness in the delta frequency and lower alpha EEG coherence in MCI patients as compared to CHI. As the cholinergic projection from the basal forebrain to the cerebral cortex is an important substratum of alpha rhythms, differences observed within this band during REM sleep could reflect the beginning of neurodegenerative changes. Support (If Any): CIHR PJT-153259.